Cavemice: The Fast and the Frozen - Book 4 4, The fast and the frozen - Stilton, Geronimo; Facciotto, Giuseppe; Heim, Julia (New York, New York Scholastic, 2014)
Geronimo Stiltons ancestor, Geronimo Stiltonoot, investigates a witnesss claim of a moving mountain of ice.
Keywords: Mice -- Fiction; Animals, Fossil -- Juvenile fiction; Glaciers -- Juvenile fiction; Mice -- Fiction; Prehistoric animals -- Fiction; Adventure and adventurers -- Fiction; Glaciers -- Fiction; Graphic novels